Caracterização e avaliação de membranas de alginato de cálcio com papaína imobilizada para o uso como curativo bioativo - Moreira Filho, Raimundo Nonato Fernandes (2021)
Natural-based dressings are of considerable interest in the pharmaceutical industry because they have low body rejection. Alginate, a polysaccharide found in the cell walls of brown algae, has excellent properties for use as biomaterial, as it is biodegradable, biocompatible and non-toxic. Alginate dressings are already a therapeutic reality, however they act only by maintaining the proper moisture of the place. In order to improve its therapeutic properties, it was proposed the incorporation of an enzyme (papain) to accelerate and improve wound healing. Papain may be found in the composition of ointments or creams for the treatment of wounds, as it is capable of promoting the debridement of the devitalized or necrotic tissues near the lesion, accelerating the healing process. The development of a dressing based on alginate and papain adds the healing properties of both materials that will potentially act to improve the healing process. The adsorption of the enzyme on a support can stabilize its structure and allow a controlled release. In the present work, papain was immobilized by physical adsorption and the best conditions for immobilization (initial concentration, temperature and pH) were evaluated and the yield of immobilization was measured by the Bradford test. It was analyzed whether the enzyme remained active after immobilization as well as measurements were taken over time to assess its stability. Desorption of the protein and its release using Franz cell was studied. Characterization tests (FTIR and SEM) and in vitro biological assays were performed (hemolysis, cytotoxicity and antibacterial). It was found that the best immobilization conditions were in neutral medium, 20 mg/mL and 25 ° C. The enzyme remained active after immobilization (5.89 U/mg) and over time it was observed that immobilized papain had a smaller decrease in relative activity compared to solution (29.15% of its initial activity versus 6.31% over 28 days). Desorption showed that 97% of the enzyme was released after 6 hours; in the Franz cell, 64.1% of the enzyme was released after 24 hours. The biological assays point to a material with low cytotoxicity and not hemolytic. Based on these initial tests, it was possible to obtain a biomaterial with good potential to be applied as a bioactive dressing.